INCIDENCE OF STROKE IN CONTEXT OF HYPERTENSION IN LOCAL POPULATION - Abro, Alla ud-Din; Abbasi, Muhammad Aslam; ., Hafeezullah; Sammo, Jawaid; Sheikh, Muzafar (Pakistan Journal of Physiology, 2007)
Background: This study was carried out to study the incidence of stroke in the people who have high blood pressure. Methods: This study was conducted on patients of stroke during 2004 at department of Medicine, Liaquat University of Medical and Health sciences (LUHMS) Jamshoro, Pakistan. Study population comprised of 100 hypertensive patients of stroke (64 men, 36 women) from different wards of LUMHS Jamshoro. Each patient was examined in detail, and investigated for blood pressure measurements, blood glucose, blood urea, serum creatinine, electrocardiogram and, CT scan of brain. A hypo dense and hyper dense area on CT scan of brain was labeled as infarction and hemorrhage respectively. The stroke patients due to other risk factors or not confirmed by CT scan were excluded from study. Results: Nearly three quarters of patients (74) who exhibits stroke were suffered from raised blood pressure. Out in two type’s i.e. hemorrhagic and infarctive stroke, the maximum number (36) of patients belongs to severe hypertension (p<0.05). Site wise putamen and hypothalamus were the chief anatomical sites suffered in hemorrhagic stroke (p<0.8), while almost all (46) patients showed infarction at corona radiata and internal capsule. Virtually every one was (88) displayed complete stroke. Conclusion: Cerebral hemorrhage is more common in hypertensive stroke patients as compared to cerebral infarction and hypertension is most common modifiable risk factor for stroke.